Odpowiedzi

Najlepsza Odpowiedź!
2010-03-03T16:41:15+01:00
A) abc-(abc-(-xyz - ( xyz - abc))) = abc-(abc-(-xyz - xyz +abc))= abc-(abc+xyz +xyz -abc)= abc-abc- xyz -xyz +abc= abc - 2xyz



b) )s²t - (st² - (s²t - (st² - s²t))) = s²t - (st² - ( s²t - st²+ s²t)) = s²t -( st²- s²t +st² - s²t)) = s²t - st²+ s²t - st² + s²t = 3 s²t - 2 st²

c) x²yz - (xy²z - (xyz² - ( x²yz - xy²z))) = x²yz -(xy²z - (xyz² - x²yz +xy²z)) = x²yz -(xy²z -xyz² + x²yz -xy²z) = x²yz -xy²z +xyz² - x²yz +xy²z = xyz²
11 4 11
2010-03-03T16:47:19+01:00
A) abc - (abc - (- xyz - (xyz - abc )))= abc-(abc-(-xyz-xyz+abc))=abc-2xyz

b)s²t - (st² - (s²t - (st² - s²t)))= s^t-(st^-(s^t-st^+s^t))=s^t-(st^-2s^t+st^)=
=s^t-2st^+2s^t=3s^t-2st^

c)x²yz - (xy²z - (xyz² - ( x²yz - xy²z))) = x^yz-(xy^z-(xyz^-x^yz-xy^z))=
=x^yz-(xy^z-xyz^+x^yz+xy^z)=x^yz-xy^z+xyz^-x^yz-xy^z=xyz^-2xy^z


^ oznacza do kwadratu
7 3 7